Simultaneous determination of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, novolac glycidyl ether and their derivatives in canned fishes by matrix solid dispersion with ultra high performance liquid chromatography-tandem mass spectrometry - Lapviboonsuk, Jutathip; Lapviboonsuk, Sompop (Bulletin of Applied Sciences, 2022)
A method was successfully developed for the simultaneous determination of thirteen monomers, i.e. bisphenol A diglycidyl ether (BADGE), bisphenol F diglycidyl ether (BFDGE), novolac glycidyl ether (NOGE 3-6 ring) and their derivatives (BADGE•H2O, BADGE•2H2O, BADGE•HCI, BADGE•2HCI, BADGE•H2O•HCI, BFDGE•2H2O and BFDGE•2HCl) in canned foods. Liquid chromatography with tandem mass spectrometry (LC-MS/MS) and matrix solid dispersion method known as QuEChERS were investigated and validated to obtain a reliable method for the application of concentration measurement. The method validation was performed according to Eurachem Guide: 2014 using fortified samples at five different concentration levels (0.025, 0.50, 1.00, 9.00 and 18.0 mg kg-1 ). The extraction recoveries ranged from 60.8 to 114.2% at 0.025 mg kg-1, 81.2 to 109.3% at 0.50 mg kg-1, 80.1 to 109.2% at 1.00 mg kg-1, 83.7 to 110.0% at 9.00 mg kg-1 and 84.6 to 109.1% at 18.0 mg kg-1 with good repeatability (%RSD ≈ 1.13-19.5). The limits of detection were 0.010 mg kg-1 for all monomers, while the limits of quantitation were the same at 0.025 mg kg-1 for all analytes. The calibration curves were provided linear up to 1000 µg L-1 with the excellent coefficient of determination (r²) in the range 0.9983-0.9999.